The Spatial Economics Practices Dilemma in Affordable Housing Construction Units Project - Azman Shah, Mohammad Alif Mifzal; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
The prevailing challenge of housing overhang poses a considerable obstacle for developers in the present day. This issue is rooted in the spatial economic strategies applied within a nation’s housing market especially affordable scheme. The primary hurdle emerges from the situation were, despite intensive advertising endeavours, a segment of the existing housing inventory lacks appeal to potential buyers, leading to the surplus of unsold properties. This study aimed to uncover issues and remedies in spatial economic practices within housing construction units. In a nation poised for economic growth, providing suitable and affordable housing is crucial. Therefore, the objectives are follows; To identify the spatial economic practice problems in the affordable housing construction units, to identify the solution for spatial economic practice problems in the affordable housing construction units and to analyse the relationship between main spatial economic practice with main solutions for spatial economic practice problems in the affordable housing construction units. The study involves housing developers company operating in the state of Johor Bahru. A quantitative approach has been employed, utilizing online survey forms and physical meetings with a sample of 113 developer in Johor Baharu. 48% response rate from 54 analysed data set has been collected out of 115 sets of questions that have been distributed. Frequency analysis, descriptive statistics, and crosstabs has been used to accomplish the study’s objectives. Upon completing the study, several objectives were successfully met. The primary main problem practice identified was the "Iterative reaction of agents on the observed situation". Concerning solutions, “Spatial Clustering Analysis” emerged main as the top choice Additionally, the main practice Iterative reaction of agents on the observed situation (Lead to increased housing price) with main solution “Market study and survey (Insight preference of potential homebuyers) is the strongest relationship”. Ultimately, this research has provided valuable insights to developers regarding the main challenges and potential solutions for addressing the problem of housing overhang in affordable housing, considering the spatial economics of homeownership. Framework development from this study can give guideline to uncover issues and remedies in spatial economic practices within housing construction units.